Marked Multiple Tendinitis at the Onset of Rheumatoid Arthritis in a Patient with Heterozygous Familial Hypercholesterolemia: Ultrasonographic Observation - Takeshi Suzuki; Akiko Okamoto (Case Reports in Rheumatology)
A 59-year-old woman who had been diagnosed with heterozygous familial hypercholesterolemia developed rheumatoid arthritis (RA). She presented with marked tendinitis of the Achilles tendons, patellar tendons, and finger extensor tendons at the onset of RA. Ultrasonographic examination revealed that tendon lesions were predominantly tendinitis rather than paratenonitis, and that the tendinitis was of the noninsertional variety, rather than the insertional variety. Preexisting tendon xanthomas might have contributed to the unusually dominant noninsertional tendinitis of multiple tendons.